+0  
 
+5
705
3
avatar
solve -6b + 1 + 4b = -3b + 6
Guest Jan 29, 2012
 #1
avatar+11 
0
-2b+1=-3b+6
b+1=6
b=5
nessapierce9  Jan 30, 2012
 #2
avatar+3079 
0
nessapierce9:

-2b+1=-3b+6
b+1=6
b=5



correct

[input]-6b + 1 + 4b = -3b + 6[/input]
admin  Jan 30, 2012
 #3
avatar
0

-6b+1+4b=-3b+6

(-6b+3b+4b)=(6-1)

b=5

Guest Jun 23, 2015

8 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.